A novel approach to synthesizing sodium antimonate and recovering lead and zinc from arsenic-bearing antimony white. (February 2023) - Tang, Zanlang; Tang, Xincun; Xiao, Zeyu; Liu, Haonan
Highlights: Sb2 O3, As2 O3, and PbO convert into NaSb(OH)6, AsO4 3-, and HPbO2 - in oxidation. Qualified NaSb(OH)6 was synthesized from raw materials by optimizing parameters. Na3 AsO4 ·12H2 O, PbS, and ZnS were precipitated from the sulfurized crystallization. Arsenic was leached by a water–leaching process to recover valuable PbS and ZnS. Abstract: In this paper, in order to eradicate the high energy consumption, environmental pollution of As2 O3 dust and hazardous arsenic–alkali residue in a traditional arsenic–bearing antimony white (A–BAW) disposal in pyrometallurgical process of jamesonite, a novel aqueous alkaline oxidation was proposed to directly synthesize sodium antimonate and recover valuable Pb and Zn. Based on the thermodynamic analysis and experimental research, sodium antimonate was prepared at [NaOH] = 8 mol/L, η[H2 O2 ] = 1.4, ratio of liquid to A–BAW = 3:1, and reaction temperature = 80 °C. The as–prepared NaSb(OH)6 was a cubic structure having a uniform size of 5–10 um. The mother liquor was purified at 2.0 times of theoretical Na2 S dosage and 10 °C as a result of PbS, ZnS and Na3 AsO4 ·12H2 O richened in crystal slags with the precipitation ratios of 99.64 % (Pb), 99.75 % (Zn) and 95.81 % (As), respectively. Furthermore, PbS and ZnS were effectively recovered by water–leaching with precipitation ratios for 99.99 % (Pb) and 99.98 % (Zn). This novel approach not only comprehensively recovers valuable metals and eliminates arsenic pollution but also realizes an economically sustainable utilization of antimonial resources from the pyrometallurgical process of jamesonite.